Development and evaluation of OmniWalker for navigating immersive computer based mine simulations - Suryajaya, M.; Fowler, C.; Lambert, T.; Stothard, Phillip; Laurence, D.; Daly, Chris (SIMTECT, 2010)
The University of New South Wales, School of Mining Engineering is performing research using experimental OmniWalker platform for Navigating Immersive Computer Based Mine Simulations. This driver for this project is that many computer based simulations rely on conventional navigation methods such as a joystick and keyboard to enable the user to navigate around the virtual environment. In most cases, this constrains the user and prevents them from actually walking around in the synthesized environment as they would in a real environment. In some instances of safety oriented simulations this may create a false impression of the difficulty of the tasks to be undertaken and the complexity of the environment. The research has found that many state-of-the-art locomotion systems such as omnidirectional treadmills have a huge barrier to entry due to the high cost of ownership. In some cases, safety may also be an issue as the slow response of such mechanical devices renders them unable to adjust to with sudden changes in walking speed. In this paper, the University of New South Wales, School of Mining Engineering presents a preliminary study of our recently-developed OmniWalker in terms of its effectiveness in delivering improved VR simulation. The device itself is relatively inexpensive and very robust for regular usage. The paper presents details of system development and of a preliminary study on the effectiveness of the OmniWalker in underground coal safety training.